A SEMIOTIC ANALYSIS CONSTRUCTION OF INDONESIAN SOLIDARITY PARTY TELEVISION ADVERTISING (Absurd Advertising Version of PSI) - OKTAVIANUS KLAU LEKIK (Metakom, 2019)
Nowadays, politics can be interpreted as a drama of life in which symbolic play takes place. In its development politics has become part of a public drama that uses theater news to stage the role played by political actors. Drama in this context can be understood as a social process in which things happen to the audience because of the parts played by the actors. This research focus on the television advertising absurd version of the Indonesian Solidarity Party, using the foundation of Charles Sanders Pierce's semiotic theory. From this study, it was concluded that the party's television adverts were only a strategy to portray themselves, raising the prestige and electability of the party alone. In the sense that the advertisement utilizes the trend of millennial which is developing rapidly so that it creates sympathy for the community, women, especially millennials Keywords: PSI Political Parties, TV Ads, Semiotics.